2017
DOI: 10.1007/s00705-017-3241-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of bovine leukemia virus from Moldovan dairy cattle

Abstract: Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL), a disease that has worldwide distribution. Whilst it has been eradicated in most of Western Europe and Scandinavia, it remains a problem in other regions, particularly Eastern Europe and South America. For this study, in 2013, 24 cattle from three farms in three regions of Moldova were screened by ELISA and nested PCR. Of these cattle, 14 which were PCR positive, and these were molecularly characterized based on the nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…The Env mutations in the South African isolates appeared to be concentrated in the conformational epitopes (F, G and H) and the ND2. These results are consistent with previous studies showing that the G epitopes, particularly residues 48, 74 and 82, are under positive selection and are the most polymorphic sites [ 51 , 73 , 74 , 75 ]. Homology modelling of the BLV Env protein has suggested that the conformational epitopes and the neutralising domains are located on the surface of the virus [ 14 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…The Env mutations in the South African isolates appeared to be concentrated in the conformational epitopes (F, G and H) and the ND2. These results are consistent with previous studies showing that the G epitopes, particularly residues 48, 74 and 82, are under positive selection and are the most polymorphic sites [ 51 , 73 , 74 , 75 ]. Homology modelling of the BLV Env protein has suggested that the conformational epitopes and the neutralising domains are located on the surface of the virus [ 14 , 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, these substitutions have previously been observed in other BLV strains of genotype 6 indicating their genotype specificity (Lee et al., ; Polat, Takeshima et al., ). Substitutions at other residues within epitope G has been observed also in some other BLV genotypes indicating its role in virus evolution and generation of escape mutants (Pluta et al., ; Polat, Takeshima et al., ; Zhao & Buehring, ). Although in general BLV env gene is subjected to negative selection, strong positive selection has been reported in residues of epitope G (Zhao & Buehring, ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the gp51 region has been widely used for BLV genotyping and phylogenetic studies for the identification of viral strains isolated from different geographical regions. Globally, at least 11 different genotypes have been identified [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%